Importance of ETO Sterilization in the Modern Era- A Review. - Sharma, Viney; Mishra, Pawan; Sharma, Suman; Singh, Narinder (International Research Journal of Ayurveda & Yoga, 2023)
Introduction- Model sterilizations of genuine medical device items with a known composition showed to be more effective than evaluation in medical devices from medical institutions for research of the behavior of various polymers in the sterilization process. Aim and Objective- To study the importance of eto-Sterilization in the Modern Era. Material and Methods- Various modern text books, Journals and websites were referred for this study. Discussion and Conclusion- Ethylene oxide gas is typically used to sterilize disposable medical equipment. When this sterilization technique is utilized, the medical devices still contain ethylene oxide (EO) and its byproducts, ethylene chlorohydrin (ECH) and ethylene glycol (EG), following sterilizations. These residues have the potential to irritate skin or mucous membranes and induce hemolytic activity in humans if their concentration is high. EO, or ethylene oxide, is a widely used sterilizing agent. Based on its variety of uses in the fields of innovative medical device development and sterilizations, its use has, however, only recently become much more prevalent. The progress made in EO sterilizations is discussed in this work, which comes to the conclusion that it is still a viable area to research and advance.